Perilaku Pencegahan Hipertensi pada Usia Produktif dalam Germas di Puskesmas Manggala Kecamatan Pinoh Selatan - Dian Indahwati Hapsari; Evi Yufiana (Yayasan Literasi Sains Indonesia, 2023)
Hypertension is a medical condition where the blood pressure is chronic, which is over 140/90 mmHg. Data for hypertension sufferers in Melawi Regency in 2019 were 3,223 people, 3,843 people in 2020 and 4,042 people in 2021. The Healthy Family Index of hypertension sufferers who seek regular treatment in Pinoh Selatan District in 2020 is 18.01%, the achievement will decrease in 2021 to 17.82% and until August 2022 it will only be 17.39%. The aim of this study was to find out the factors related to hypertension prevention behavior at productive age in the community movement for healthy living (GERMAS) at the Puskesmas Manggala, Pinoh Selatan sub-district in 2022. This study used a cross sectional design. The population is the productive age range (15-59 years) in the working area of the Manggala Health Center, Pinoh Selatan District, Melawi Regency in 2022, a sample of 189 was taken using a proportional random sampling technique. The statistical test used is the chi-square test with a confidence level of 95%. The results showed that there was a significant relationship between the physical activity of respondents and the behavior of preventing hypertension at productive age in the Germas program (p-value = 0.046), consumption of alcohol (p-value = 0.021), eating fruit and vegetables (p-value = 0.036 ). Variables that are not related are routine health checks every month (p-value = 0.746) and smoking (p-value = 0.057). It is suggested to the Melawi District Health Office to improve the program to encourage and support the puskesmas program to screen PTM with Germas guidelines, provide information and education communication advice, advocacy to relevant agencies and the Puskesmas to provide consultative guidance regarding hypertension to people of productive age.